Best versus worst surgical outcomes after single-level posterior lumbar interbody fusion for degenerative spondylolisthesis. (15th February 2021) - Park, Se-Jun; Lee, Keun-Ho; Lee, Chong-Suh; Kim, Ki-Tack; Kim, Dong Hyeon; Lee, Chae Ho; Kim, Gab-Lae
Purpose: Previous studies have shown conflicting results regarding the factors affecting the clinical outcome after fusion for degenerative spondylolisthesis. However, no study has compared the best and worst clinical outcome groups using patient-reported outcome measures. We aimed to compare the characteristics of patients with best and worst outcomes following single-level lumbar fusion for degenerative spondylolisthesis. Methods: 200 patients underwent single-level interbody fusion with a minimum 2-years follow-up were included. We excluded patients with surgical complications already-known to be associated with poor postoperative outcomes, including pseudoarthrosis and postoperative infection. According to 2-year postoperative Oswestry disability index scores, patients were divided into two groups; Best and Worst. Demographic, clinical and radiographic variables were compared between the two groups. Results: Compared with patients in the Best group, those in the Worst group were older (59.5 and 67.0 years, respectively; p = 0.012; odds ratio [OR], 1.143; 95% confidence interval [CI], 1.030–1.269) and had a longer duration of pain from onset (2.6 and 7.2 years, respectively; p = 0.041; OR, 1.021; 95% CI, 1.001–1.041). The cutoff value of pain duration from onset was measured as ≥3.5 years on Receiver operating characteristic analysis. Patients in the Worst group had a lower preoperative angular motion compared to those in the Best group (12.7° and 8.3°, respectively; p = 0.016; OR, 0.816; 95% CI, 0.691–0.963). Conclusions: Degenerative spondylolisthesis patients of good clinical outcome after single-level lumbar interbody fusion were relatively young, had a short symptom duration before surgery, and a high preoperative instability compared with the patient having poor postoperative clinical outcome. Therefore, these findings should be considered preoperatively when deciding the appropriate individual treatment plan.